Is the Post-Reformation System of the Indonesian Government a Parliamentary Form? - Sinaga, Parbuntian; Machmud, Aris (International Journal of Law Reconstruction, 2024)
Indonesia's democratic government system has experienced ups and downs based on history, where at the beginning of independence Indonesia used a presidential system, then changed to a parliamentary and then returned to a presidential system. The reformation period was a milestone in changing the government system where previously the president was elected by the MPR as the highest state institution to switch to direct presidential elections carried by a party or a coalition of parties - due to the existence of regulation on the threshold for nomination (parliamentary threshold) - but to maintain the implementation of the presidential campaign promise to establish a coalition of parties supporting the government which has an impact on the role of the People^s Representative Council only as a stamp of government interests. The problem in this study is how the presidential system exists in the post-reform Indonesian government system. The form of the research method used is normative juridical with a statutory approach and an analytical descriptive approach that examines primary and secondary legal materials, besides examining the synchronization and harmonization of law. The conclusion is that the current Indonesian government system tends to be parliamentary. This is due to the weak bargaining position of the DPR in supervising the running of government because the majority of DPR members are supporters of the government, while the opposition forces are unequal with the majority, which prioritizes the most voting system over consensus deliberation for the benefit of the people. so that checks and balances - separation of powers - turned into a division of powers - dividing power.